Implementation of Change Islamic Management in Improving the Quality of Scientific Journal Management - Ghanatika, Gadis; Rofiq, Ainur; Susilowati, Christin (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
The lack of reputable scientific journals in Indonesia has prompted the government to implement bureaucratic reforms for national scientific journal accreditation. This change forces scientific journal managers to change their management model in accordance with technological developments and changing consumer demands. This research was conducted to reveal and explain the implementation of change management in the management of scientific journals in Indonesia, namely: TEFLIN (SCOPUS Q3), Bahasa dan Seni (SINTA 2), and Basindo (SINTA 4). This research uses a quantitave approach with a multi-case study method. The result showed that changes in the management of scientific journals from print models to electronic models were possible because they were supported by the following factors: (1) conducive external and internal driving factors, (2) supportive organizational potential, (3) a strong agent of change, and (4) the use of the right strategy.